Kekerasan Pada Tokoh Perempuan Dalam Novel Minoel Karya Ken Terate - Rafiqaty Esa Putri; M. Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This research will describe the violence against women that can be seen physically and verbally in Ken Terate's novel Minoel. This research uses a type of literary research that was developed using descriptive methods. The data source is Minoel's novel, written by Ken Terate. The data were analyzed in the following ways: 1) classifying data, 2) then interpreting it by connecting findings with reality while criticizing the results of the analysis carried out and connecting them with existing theories, and 3) concluding the data analysis and writing reports on the results of the analysis. However, the data will be checked beforehand to avoid errors. The results of this study indicate the forms, causes, and impacts of violence against women.